So you want to host a multi-stakeholder platform? Designing meaningful, inclusive spaces for transformative change - Larson, A.M.; Sarmiento Barletti, J.P. (CIFOR-ICRAF, 2023)
Multi-stakeholder platforms (MSPs) are participatory processes that include a wide range of actors in a topic or a landscape, to engage in dialogue, decision making, and/or the implementation of activities for common (landscape) goals.